Effects of laminate stacking sequence on the strength properties of aluminum alloy–carbon fiber-reinforced plastic dissimilar single-lap adhesive joints - Kazuhiro kusukawa (Journal of Advanced Joining Processes)
Here, two single-lap adhesive joints (SLJs) of dissimilar materials were subjected to static and cyclic loading tests. A2017 aluminum alloy was used as an adherend for one, and carbon fiber reinforced plastic (CFRP) was used as the adherend for the other. Four types of orthogonal laminated CFRPs with different laminate stacking sequences were used as adherends to investigate the effect of adherend stiffness on the strength properties of the joints. Furthermore, the results of the finite element analysis of the dissimilar SLJs revealed that when the tensile load was applied to them, the out-of-plane deformation asymmetry increased with increasing difference in stiffness between both adherends. This asymmetry affected the peel and shear stress distributions. Furthermore, the experiments revealed that the static tensile strength of the SLJs increased with increasing stiffness of the CFRP adherend. Additionally, fracture simulation using cohesive-zone modeling (CZM) revealed that the SLJs with higher CFRP stiffness exhibited higher strength, qualitatively agreeing with the experimental results. CZM analysis and adhesion strain measurements during the tests indicated that failure occurred at the A2017 adherend–adhesive interface. In contrast, no differences were observed between the fatigue strengths of the different types of adherends in the short-life region, with a number of cycles to failure (Nf) being ≤ 2 × 105. However, in the long-life region, beyond Nf = 2 × 105, the SLJ bearing the unidirectional CFRP adherend exhibited lower fatigue strength than the others. The anodizing process on A2017 was found to improve fatigue strength by a factor of two or more.